Evaluation of the tracing effect of carbon nanoparticle and carbon nanoparticle-epirubicin suspension in axillary lymph node dissection for breast cancer treatment. Issue 1 (December 2016) - Du, Junze; Zhang, Yongsong; Ming, Jia; Liu, Jing; Zhong, Ling; Liang, Quankun; Fan, Linjun; Jiang, Jun
Abstracts Background Carbon nanoparticle suspension, using smooth carbon particles at a diameter of 21 nm added with suspending agents, is a stable suspension of carbon pellets of 150 nm in diameter. It is obviously inclined to the lymphatic system. There were some studies reporting that carbon nanoparticles are considered as superior tracers for sentinel lymph nodes because of their stability and operational feasibility. However, there were few study concerns about the potential treatment effect including tracing and local chemotherapeutic effect of carbon nanoparticle-epirubicin suspension on breast cancer with axillary metastasis. Methods In the current study, a randomized controlled analysis was performed to investigate the potential treatment effect of carbon nanoparticle-epirubicin suspension on breast cancer with axillary metastasis. A total of 90 breast cancer patients were randomly divided into three equal groups: control, tracer, and drug-load groups. The control group patients did not receive any lymphatic tracers, the tracer group patients were subcutaneously injected with 1 ml carbon nanoparticle suspension, and the drug-load group patients were injected with 3 ml carbon nanoparticle-epirubicin suspension at four separate sites around the areola 24 h before surgery. Modified radical mastectomy, endoscopic subcutaneous mammary resection plus axillary lymph node dissection, and immediate reconstruction with implants or breast-conserving surgery were performed. Results The mean number of the dissected lymph nodes per patient was significantly higher in the tracer (21.3 ± 6.1) and drug-load (19.5 ± 3.7) groups than in the control group (16.7 ± 3.4) (P  < 0.05). Most lymph nodes in the former two groups were stained black (75.7 and 73.3 %, respectively), but with no significant difference between the groups. Most metastatic lymph nodes were also stained black in the tracer group (68.6 %) and drug-load group (78.1 %) and with no significant difference between the groups (P  = 0.198). Microscopic examination revealed that the carbon nanoparticles were localized around or among the cancer cell masses and residues of necrotized cancer cells surrounded by fibroblastic proliferation could be found within the stained lymph nodes in the drug-load group. Conclusions The majority of axillary lymph nodes were stained black by the suspension of carbon nanoparticles, which helped identify the lymph nodes from the surrounding tissues and avoided aggressive axillary treatment. Thus, a combination therapy of carbon nanoparticles with epirubicin could play an important role in lymphatic chemotherapy without affecting tracing. Trial registration ChiCTRTRC13003419